A comunidade latino-americana de Nações - (C.F., parágrafo único, art. 4º): o paradigma da União Européia - Berardi, Luciana Andrea Accorsi (2010)
This study analyzes two paradigms of regional integration, the European Union, and the most advanced model proposed by Latin America, from the structuring of MERCOSUR. Straightforward glimpse the possibility of developing an American community of Nations and their integration. As a result, demonstrate the possibility to consolidate this community, as prescribed in single paragraph of art. 4, from the 1988 Federal Constitution. Under this visionary constitutional command, bring a Constitution transnational materializing the dream of Simon Bolivar, but now under a new Prism: differences in tribute to the right of coexistence. To achieve this purpose, first, this work will be weighed the fundamental elements of federalism. After, on the theme of our Institute of sovereignty, because in the different models of integration, there may be greater or lesser sharing then consider integration itself, origins, stages and development of their varied conceptions, until you reach the phenomenon of globalization, as undoubtedly intersection economical, political, social and even cultural Nations. Further, using the European Union as paradigm and supranational model and integration, MERCOSUR as an example, compare the development of both to demonstrate the necessity of improving the consolidated proposals in on UNASUR and CELAC, having thus viewed the formation of a Constitution for the Latin American community of Nations, distinct from the former European institution, noting the differences between Latin States; respecting their cultures; while singing new praises as beams, the dignity of the human person, respect for the environment and pluralism; increasing the notion of "belonging" to a community on behalf of peace, solidarity and social justice. And thus broaden economic wealth; promote the human development so that they can cope with the strong winds of globalization under a cohesive roof